2020
DOI: 10.3390/ijms21134623
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives in Manipulating EVs for Therapeutic Applications: Focus on Cancer Treatment

Abstract: Extracellular vesicles (EVs) receive special attention from oncologists due to their assumed usefulness as prognostic markers, vaccines to induce anti-cancer immune response, and physiological delivery tools. The latter application, which supports the reduction of side effects of treatment, is still fraught with many challenges, including established methods for loading EVs with selected cargo and directing them towards target cells. EVs could be loaded with selected cargo either in vitro using several physico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 127 publications
(174 reference statements)
0
18
0
Order By: Relevance
“…We showed that monovalent antibody against CD9 can impede the entry of EVs into melanoma cells [ 91 ]. Further efforts are needed to dissect all mechanisms regulating the specificity of EV-recipient cell interactions, which is an important step to design new strategies based on EVs as a bio-vehicle for therapeutic drug delivery [ 92 , 93 , 94 ].…”
Section: Extracellular Membrane Vesicles and Intercellular Communimentioning
confidence: 99%
“…We showed that monovalent antibody against CD9 can impede the entry of EVs into melanoma cells [ 91 ]. Further efforts are needed to dissect all mechanisms regulating the specificity of EV-recipient cell interactions, which is an important step to design new strategies based on EVs as a bio-vehicle for therapeutic drug delivery [ 92 , 93 , 94 ].…”
Section: Extracellular Membrane Vesicles and Intercellular Communimentioning
confidence: 99%
“…An alternative to modifying parental cells is the direct incorporation of specific molecules (i.e., miRNA, siRNA, protein, lipids, drugs) into EVs through passive or active methods ( Luan et al, 2017 ; Sterzenbach et al, 2017 ; Nasiri Kenari et al, 2020 ; Nazimek and Bryniarski, 2020 ). Incubation of EVs with active components is a passive method of loading that involves the diffusion of drugs or molecules with varied encapsulation efficiency through the EV membrane.…”
Section: Engineered Evsmentioning
confidence: 99%
“…Surface modification with polyethylene glycol (PEG) is the most common approach among these strategies [ 60 ]. Antigen-specific antibody light chains could coat the surface of EVs to increase cell targeting specificity, while EV membrane lipids may possess immune adjuvant activity [ 62 ]. Engineering EVs to functionalize and enclose molecules or nanoparticles, for imaging or therapy purposes are shown in Figure 3 .…”
Section: Modification Of Exosomes For Imaging and Theranostic Applmentioning
confidence: 99%
“…This could represent a critical advance forward to the disclosing of exosome homing and, more broadly, TEX in pathological conditions. The route of EV administration determines bioavailability and affects its therapeutic effect [ 62 ]. Despite advances in exosome modification strategies, there are still many challenges to overcome to effectively harness their therapeutic potential.…”
Section: Future Perspectives Of the Exosomes In Imaging And Theranmentioning
confidence: 99%